AB0581 Anti-tnf drug survival in psoriatic arthritis patients treated in ordinary clinical practice. (23rd January 2014) - Haugeberg, G.; Gulati, A. M.; Diamantopoulos, A. P.; Hoff, M.; Kavanaugh, A.
Abstract : Background: The use of TNF-inhibitors in psoriatic arthritis (PsA) has been sh own to improve clinical and radiographic outcome in randomized controlled trials (RCT) and shown to be well tolerated with a rather low rate of drop outs. However, patients in RCT may not be representative of patients followed in ordinary clinical practice. Objectives: To assess drug survival of TNF-inhibitor treatment in patients with PsA treated in an ordinary rheumatology clinic in Norway. Methods: The PsA patients were recruited from an ordinary rheumatology clinic in Norway. All PsA patients in this clinic are monitored and outcome measures and drug data is registered in a clinical hospital computer database. In the database termination and/or change of therapy had been registered. A survival analysis (Kaplan-Meyer) was performed and survival time for sequential therapeutic regimens were compared by Wilcoxon test. Anonymised data was analyzed using SPSS. Results: We identified 148 patients with PsA who started treatment with their first TNF-inhibitor (from 2002 through 31.12.2012). During the first year of therapy 52 (35%) of these patients stopped treatment. 54 patients started their second and 22 patients started their third or more TNF-inhibitor, and within the first year 33 (61%) and 12 (55%), respectively, stopped treatment. The rate of patients who stopped treatment was highest in the beginning and lover during follow up. This was also seen for the second and ≥ 3 rd TNF inhibitor. Overall drug survival was significantly higher for the first TNF-inhibitor compared to the second drug (p<0.001; fig. 1 ). The median survival time for the first, second and subsequent drug was 24, 7, and 9 months. Image/graph: Conclusions: In an ordinary clinic setting, patients with PsA have a significantly reduced drug survival for the subsequent TNF-inhibitor if they fail on the first drug. For each drug, the first year of treatment had the highest termination rate. References: Mease P et al. Arthritis Rheum 04;50:2264-72. Kavanaugh A et al. ARD 07;66:498-505. Disclosure of Interest: G. Haugeberg Shareholder of: and founder of DiaGraphIT manufacturing the GoTreatIT computer system, Grant/research support from: Urestricted research grant from Pfizer, A. Gulati: None Declared, A. Diamantopoulos: None Declared, M. Hoff: None Declared, A. Kavanaugh: None Declared